How does Leaders’ Aversiveness Effect Employees’ Life Satisfaction? Moderation of Emotional Resilience - Ali, Maryam; Yasmeen, Nasira; Kayani, Muhammad Bilal (UW Journal of Management Sciences, 2023)
Purpose: The current study investigates the impact of aversive leadership on employee life satisfaction with the moderation of emotional resilience. The study is conducted on service sector employees as being the major contributor to economic growth. Design and Methodology: The study was conducted cross-sectionally with a sample of 350 in Pakistan using the convenience sampling method. Findings: The current study discovered that aversive leadership has a significant negative impact on employee life satisfaction. As aversive leaders practice threatening and intimidation leading to employee stress at work and at home. Moreover, employees with the ability of emotional resilience were found to be better at handling their leaders’ aversion, reducing their life stress and dissatisfaction. Implications: The current study provides significant literature and helps practitioners better judge these aspects in humans when hiring and handling. Keywords: Destructive Leadership Aversive Leadership, Life Satisfaction, Resilience and Emotional Resilience.